THE EFFECT OF PHYSICAL PROGRAMMING EXERCISE ON BDNF SERUM RECEIVER ON LANSIA IN HEALTHY HEALTH CLUB PALEMBANG - Hasbullah, Ade (Sriwijaya University Learning and Education International Conference, 2018)
Along with the age increase, most elder people are lazy to exercise, doing physical activity regularly and periodically will make the cognitive function better . When performing physical activity, the brain will be stimulated to increase the protein in the brain called Brain Derived Neutrophic Factor. BDNF is an important role to keep the nerve cells healthy and fit. The aim for this study is to analyze the influence of programmed physical activity on BDNF serum levels in elderly people at healthy heart palembang clubs. This study is a Cross Sectional research with sample used are elderly people who regularly do programmed physical activity at Club Jatung Sehat Kambang Iwak Palembang Branch. Sample in this Research are the healthy elderly and are over 60 years old, in total of 25 people. Result of analysis of the influence between the level of physical activity with the function of BDNF serum level in elder people was obtained and shows that respondents with regular physical activity have a good level of BDNF serum. The statistical test result obtained shows a significant increase of BDNF levels ( p = 0,014 ) thus can be concluded that there are influence among activity level against BDNF serum levels on elderly.